2020
DOI: 10.1093/gbe/evaa091
|View full text |Cite
|
Sign up to set email alerts
|

Plastid Genome Evolution in the Subtribe Calypsoinae (Epidendroideae, Orchidaceae)

Abstract: Calypsoinae is a small subtribe in Orchidaceae (Epidendroideae) characterized by diverse trophic strategies and morphological characters. Calypsoinae includes 13 genera, four of which are leafless and mycoheterotrophic. Mycoheterotrophic species in the leafless genus Corallorhiza are well suited to studies of plastome evolution. However, the lack of plastome sequences for other genera in Calypsoinae limits the scope of comparative and phylogenetic analyses, in particular our understanding of plastome evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
3
25
0
2
Order By: Relevance
“…The monograph indicated that the mentum is one of the characters to distinguish C. striata and other congeneric species ( Freudenstein, 1997 ), thus the character presents a possible synapomorphy for the clade. Our phylogenetic result is consistent with the previous studies ( Kim et al., 2020 ; Li et al., 2020 ), that Corallorhiza is not a monophyletic group, because the genus Oreorchis is nested within the clade of Corallorhiza with strong bootstrap support (BS = 100) and posterior probability (PP = 1.00). In the Calypsoinae, however, phylogenetic analysis based on the nrDNA sequence suggests that Corallorhiza is a monophyletic group and strongly supports C. sinensis as sister to Corallorhiza (ML: BS = 98; BI: PP = 1.00).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The monograph indicated that the mentum is one of the characters to distinguish C. striata and other congeneric species ( Freudenstein, 1997 ), thus the character presents a possible synapomorphy for the clade. Our phylogenetic result is consistent with the previous studies ( Kim et al., 2020 ; Li et al., 2020 ), that Corallorhiza is not a monophyletic group, because the genus Oreorchis is nested within the clade of Corallorhiza with strong bootstrap support (BS = 100) and posterior probability (PP = 1.00). In the Calypsoinae, however, phylogenetic analysis based on the nrDNA sequence suggests that Corallorhiza is a monophyletic group and strongly supports C. sinensis as sister to Corallorhiza (ML: BS = 98; BI: PP = 1.00).…”
Section: Discussionsupporting
confidence: 92%
“…A total of 109 unique genes were identified in the plastome, which contains 68 protein-coding genes, 30 tRNAs, and four rRNAs. C. sinensis further shows evidence of some photosynthesis-related genes either lost or pseudogenized, which is consistent with some previous studies of Corallorhiza ( Barrett and Davis, 2012 ; Kim et al., 2020 ; Li et al., 2020 ). In the current study, a common feature of the plastome of Corallorhiza and Oreorchis species was that IR regions were more conserved than the LSC and SSC regions .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…(2020a) , for example, utilized the chloroplast genomes of 124 species of orchids to evaluate the phylogenomics and relationship within the Orchidaceae family. Moreover, the whole cp genome phylogeny that was generated at different taxonomical level in several groups of Orchidaceae, such as subtribe Aeridinae ( Kim et al., 2020b ), subtribe Calypsoinae ( Li et al., 2020 ), and Holcogloss um ( Li et al., 2019 ). Considering that most species-level diversity of Orchidaceae, a whole cp genome phylogeny is highly desired for Bulbophyllum .…”
Section: Discussionmentioning
confidence: 99%
“…Paired-end sequencing (100-bp read lengths) was performed on an Illumina HiSeq 2500 platform at Majorbio in Beijing, which generated 5 GB of raw data. We assembled the plastome according to previously described methods ( Feng et al., 2016 ; Li et al., 2020a , Li et al., 2020b ). The filtered paired reads were mapped to the plastome of G. elata (GenBank accession number: MF163256 ) using Geneious v.10.1.2.…”
Section: Methodsmentioning
confidence: 99%